Performance Evaluation of Tungsten-Based Composites as Lead-Free X-Ray and Gamma Radiation Shielding Materials Across Medical Photon Energy Ranges - Mahmoud Suleiman Dahoud (JST (Jurnal Sains dan Teknologi), 2026)
Lead-based radiation shielding has limitations in the form of high toxicity and high density, making it less safe and efficient for medical applications. Therefore, alternative radiation shielding materials are needed that are lighter, non-toxic, and remain effective across a wide range of photon energies. This study aims to evaluate the performance of tungsten-based composites as lead-free radiation shielding materials through a systematic review and numerical simulation of 110 scientific articles from 2025 to 2026, focusing on 18 tungsten composites (S1–S18). Data were collected from the literature and the Phy-X/PSD database using half-value layer (HVL) and effective atomic number (Zeff) parameters, then analyzed comparatively with lead shielding. The results show that composites with high tungsten content, especially S5, have better HVL values than lead. At low energies, non-linear behavior occurs due to the K-edge effect and the dominance of the photoelectric effect. In contrast, at high energies, the HVL increase is influenced by Compton scattering. Material density also affects the effectiveness of the shielding. It is concluded that tungsten composites have the potential to be safer and more sustainable radiation shielding materials, with the implication that optimizing composition and density is key to developing effective materials.